2021
DOI: 10.1155/2021/4338838
|View full text |Cite
|
Sign up to set email alerts
|

A Radioresponse-Related lncRNA Biomarker Signature for Risk Classification and Prognosis Prediction in Non-Small-Cell Lung Cancer

Abstract: Purpose. Radiotherapy resistance is now recognized as the major obstacle to the effective therapeutic management of non-small-cell lung cancer (NSCLC). As a single biomarker has limited effect in stratifying NSCLC patients, this research aimed to identify long non-coding RNAs (lncRNAs) correlated with radiotherapy response to ameliorate forecast of NSCLC prognosis. Methods. In a cohort of NSCLC patients with radiotherapy history (n = 96) from TCGA, genetic data of lncRNA expression profiling were performed. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The incidence of gynecological malignant cancers in pregnant women is increasing, among which, CC is the most frequently diagnosed cancer during pregnancy ( Smith et al, 2003 ; Song et al, 2021b ). Considering that gynecological screening is relatively bounded during pregnancy, efforts have been made to explore an effective prognostic model to guide the treatment for CC ( McIntyre-Seltman and Lesnock, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of gynecological malignant cancers in pregnant women is increasing, among which, CC is the most frequently diagnosed cancer during pregnancy ( Smith et al, 2003 ; Song et al, 2021b ). Considering that gynecological screening is relatively bounded during pregnancy, efforts have been made to explore an effective prognostic model to guide the treatment for CC ( McIntyre-Seltman and Lesnock, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies on the relationship between radiotherapy efficacy and lncRNAs as biomarkers for radiotherapy patients, such as in non-small cell lung cancer and glioma ( Lin et al, 2020 ; Song et al, 2021 ). However, the clinical application of lncRNAs as biomarkers of radioresistance still faces huge challenges.…”
Section: Discussionmentioning
confidence: 99%
“…However, when both systems are active (i.e., in late S and G 2 phases), NHEJ can operate when the lesion is not too complex; otherwise, there is a switch toward HR [ 27 ]. Elevated DNA repair capacity due to the overexpression of the DSB repair proteins RAD51 and DNA-PKcs confers radioresistance in different cancer cells [ 26 , 31 , 32 , 33 , 34 ]. The elevated expression of XRCC1, which is involved in the BER pathway and in SSB repair, is associated with radioresistance in patients with lung cancer and NSCLC [ 35 ].…”
Section: Molecular and Cellular Features Associated With Radioresistancementioning
confidence: 99%
“…Gene expression is modulated by the action of non-coding RNAs (ncRNAs), either long (>200 nt) or small (<200 nt), which function in the nucleus and in the cytoplasm [ 75 , 82 , 83 , 84 , 85 ]. Recent evidence has identified radioresistance-associated lncRNAs in NSCLC cells [ 32 ]. However, many studies on tumor radioresistance have reported changes in the expression of microRNAs (miRNAs), which are small, well-known ncRNAs that modulate the expression of many genes belonging to different pathways [ 86 ].…”
Section: Molecular and Cellular Features Associated With Radioresistancementioning
confidence: 99%